Pemahaman Masyarakat Dalam Melakukan Upaya Preventif Penyebaran Covid-19 Melalui Rekonseptualisasi Nilai-Nilai Qada Dan Qadar - Syaichon Ibad; Hernik Farisia; Putri Dellaika Aisyah; Bella Fitria Destinasari (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
This study aims to explain how the conditions and climate of people's understanding of qaḍā’ and qadar in the context of the current pandemic, especially in the Pereng hamlet community, Ngasin Balongpanggang, Gresik village, which is still widely misunderstood by several layers of the general public. this is the initial basis in making efforts to prevent the spread of Covid-19 (Corona Virus Diseases-19) through reconceptualization of the values ​​of qada and qadar. This research uses descriptive qualitative, namely analyzing and presenting facts systematically, so that it can be easier to understand and conclude. While the data sources are divided into two, namely primary is the original source of data obtained directly from the object of research in order to obtain definite data and secondary, data obtained in the literature by looking for information and data in the form of journals, books, and social media concerned. with public awareness in carrying out efforts to prevent the spread of COVID-19. The results of the study are that there is still a lot of destruction of meaning about qada and qadar in people's understanding which is motivated by animism and dynamism belief systems that have been held by their ancestors in the past, so that Covid-19 is then very susceptible to being transmitted from one muslim to another.